Pseudoirreversible slow-binding inhibition of trypanothione reductase by a protein-protein interaction disruptor (2020)
ABSTRACT: Background and purpose: Peptide P4 was described as a dimerization disruptor of trypanothione reductase (TryR), a homodimeric enzyme essential for survival of trypanosomatids. Determination of the true inhibitory constant (Ki ) for P4 was not achieved because reaction rates continuously decreased with time, even when substrate concentration was kept constant. The aim of this study was to find a suitable kinetic model that could allow characterization of the complex pattern of TryR inhibition caused by P4. Experimental approach: After showing the slow-binding and pseudoirreversible activity of P4 against Leishmania infantum trypanothione reductase (Li-TryR), analysis of the curvatures of the reaction progress curves at different inhibitor concentrations allowed us to define the apparent inhibitory constants (Kiapp ) at five different substrate concentrations. Analysis of the changes in Kiapp values allowed precise definition of the type of inhibition. Key results: Li-TryR inhibition by P4 requires two sequential steps that involve rapid generation of a reversible enzyme-inhibitor complex followed by a pseudoirreversible slow inactivation of the enzyme. Recovery of enzyme activity after inhibitor dissociation is barely detectable. P4 is a non-competitive pseudoirreversible inhibitor of Li- TryR that displays an overall inhibition constant (Ki* ) smaller than 0.02 μM. Conclusion and implications: Li-TryRdimer disruption by peptide P4 is a pseudoirreversible time-dependent process which is non-competitive with respect to the oxidized trypanothione (TS2 ) substrate. Therefore, unlike reversible Li-TryR competitive inhibitors, enzyme inhibition by P4 is not affected by the TS2 accumulation observed during oxidant processes such as the oxidative burst in host macrophages.